An efficient method for solving an inverse problem for the Richards equation - Bitterlich, Sandro; Knabner, Peter (Journal of Computational and Applied Mathematics, 2002)
A parameter identification problem for the hydraulic properties of porous media is considered. Numerically, this inverse problem is solved by minimizing an output least-squares functional. The unknown hydraulic properties which are nonlinear coefficients of a partial differential equation are approximated by spline functions. The identification is embedded into a multi-level algorithm and coupled with a linear sensitivity analysis to describe the ill-posedness of the inverse problem. © 2002 Elsevier Science B.V. All rights reserve
Keywords: Adjoint method; Direct method; Inverse problem; Multi-level algorithm; Parameter identification; Sensitivity analysis